Hypertensive Disorders and Pregnancy-related Stroke: Frequency, Trends, Risk Factors, and Outcomes. Issue 4 (December 2015) - Leffert, L.R.; Clancy, C.R.; Bateman, B.T.; Bryant, A.S.; Kuklina, E.V.
Abstract : ( Obstet Gynecol . 2015;125(1):124–131)